2021
DOI: 10.3390/molecules26092549
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Sensing and Removal of Heavy Metals: Bioelectrochemical Detection and Removal of Chromium(VI) and Cadmium(II)

Abstract: The presence of inorganic pollutants such as Cadmium(II) and Chromium(VI) could destroy our environment and ecosystem. To overcome this problem, much attention was directed to microbial technology, whereas some microorganisms could resist the toxic effects and decrease pollutants concentration while the microbial viability is sustained. Therefore, we built up a complementary strategy to study the biofilm formation of isolated strains under the stress of heavy metals. As target resistive organisms, Rhizobium-MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…PSIM biofilm biomass (cells/mL) the authors have reported immobilization and absorption of heavy metals by the EPS of Bacilli biofilm matrix as the principle behind this process of bioremediation [27,30]. The tolerance of Gram-negative bacteria Rhizobium toward Cr and Cd showed similar results as of our study where the microbes were able to tolerate the concentrations of 0.1 mg/mL and 1 mg/mL of heavy metals [31]. Similarly, in our study, PSIM biofilm possessed a higher ability to form EPS and to absorb the heavy metal with greater resistance, considering our Grampositive isolated microorganisms have a great potential in the removal of toxic heavy metals than the previously reported studies.…”
Section: Od At a 600 Psimsupporting
confidence: 84%
“…PSIM biofilm biomass (cells/mL) the authors have reported immobilization and absorption of heavy metals by the EPS of Bacilli biofilm matrix as the principle behind this process of bioremediation [27,30]. The tolerance of Gram-negative bacteria Rhizobium toward Cr and Cd showed similar results as of our study where the microbes were able to tolerate the concentrations of 0.1 mg/mL and 1 mg/mL of heavy metals [31]. Similarly, in our study, PSIM biofilm possessed a higher ability to form EPS and to absorb the heavy metal with greater resistance, considering our Grampositive isolated microorganisms have a great potential in the removal of toxic heavy metals than the previously reported studies.…”
Section: Od At a 600 Psimsupporting
confidence: 84%
“…Nanocomposites are materials (two or more phases) with different types or different structures engineered in nanoscale dimensions [ 21 , 84 ]. Use of nanocomposites (nanoparticles [ 85 ], nanosheets [ 86 ], or nanotubes [ 87 ]) is one of the most trending strategies in the development of impedimetric biosensors due to their unique electrochemical, mechanical, thermal, optical, and catalytic features.…”
Section: Nanocomposite-based Impedimetric Biosensorsmentioning
confidence: 99%
“…The potentiality of industrial effluents containing heavy metal ions, such as copper, chromium, lead, and nickel, toward the environment had been reported to be a cause of the virulent impact on a variety of living organisms (i.e., plants, animals, and human beings) ( Alotaibi et al, 2021 ). These metals can accumulate in tissues of animals, and also in the human body ( Alfadaly et al, 2021 ), causing disruption of cell membranes, lipid peroxidation, inhibition of oxidative phosphorylation, protein denaturation, and alteration of nucleic acids structures ( Xie et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%